How Bedrock‐Controlled Channel Migration Can Structure Selective Preservation of Archaeological Sites: Implications for Modeling Paleoindian Settlement. Issue 1 (25th November 2015) - Herrmann, Edward W.
Abstract : Although Paleoindian sites in Indiana, USA, are commonly located on late Wisconsin (Last Glacial Maximum) outwash terraces, drainage basin development since deglaciation often obscures the visibility of such sites on flood plains by either burying them under alluvium or destroying them through erosion. Significant clusters of Paleoindian and Early Archaic sites, however, have been identified proximal to the modern White River channel in central Indiana on what is mapped as "floodplain." These site cluster locations are patterned. They typically occur within bedrock‐controlled river reaches but are rare along unconfined meandering reaches. Subsurface reconnaissance and chronology indicate that despite the fact that they often flood, portions of the so‐called flood plains within bedrock‐confined reaches are actually terraces constructed of late Wisconsin outwash with minimal overbank sedimentation. Terrace preservation in these settings is a result of bedrock structure that protects older sediments from lateral erosion and differentially preserves archaeological sites near the modern channel in bedrock‐controlled reaches. Comparisons of archaeological sites within bedrock‐controlled segments of the White River to those in unconfined meandering segments suggests that significant numbers of Paleoindian and Early Archaic sites may be missing from river settings across the midcontinent. These findings demonstrate that bedrock channel controls are important to recognize when assessing prehistoric settlement distributions.